1999
DOI: 10.1890/0012-9658(1999)080[2397:lteioa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Ecosystem Impacts of an Introduced Grass in the Northern Great Plains

Abstract: Introduced plants can have negative effects on native species and diversity, but their impacts on ecosystem function are less apparent. At the northern edge of the Great Plains, we examined five stands in each of undisturbed prairie, successional prairie (fields abandoned for ∼50 yr that had undergone succession to native grasses), and abandoned fields of similar age planted with Agropyron cristatum, a C3 perennial tussock grass introduced from northern Asia. We attributed differences between successional prai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
132
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(139 citation statements)
references
References 39 publications
6
132
1
Order By: Relevance
“…More fires may act synergistically with N deposition and the invasion by exotics to alter vegetation structure [86]. For example, many drylands are being invaded by exotic species, a process that reduces ecosystem functioning [90] and is expected to be further worsened with global change [91]. Moreover, the productivity and cover of these exotics has also been reported to be enhanced with N deposition [92].…”
Section: Global Environmental Change Effects On Drylandsmentioning
confidence: 99%
“…More fires may act synergistically with N deposition and the invasion by exotics to alter vegetation structure [86]. For example, many drylands are being invaded by exotic species, a process that reduces ecosystem functioning [90] and is expected to be further worsened with global change [91]. Moreover, the productivity and cover of these exotics has also been reported to be enhanced with N deposition [92].…”
Section: Global Environmental Change Effects On Drylandsmentioning
confidence: 99%
“…In addition to sharing similar processes and dynamics, the processes of succession and species introductions may directly interact and affect one another. For example, if non-indigenous species significantly affect key ecosystem attributes or processes (Hobbs and Huenneke 1992;D'Antonio and Vitousek 1992;Vitousek et al 1997;Christian and Wilson 1999), they may affect historical successional patterns and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The old fields and native environments differ in their dominant grass species, with the native savannas and grasslands dominated by native warm-season grasses and the old fields normally dominated by introduced European cool season grasses. Grass effects on woody plants can vary depending on the grass species involved (Gordon et al 1989;Rice et al 1993) and some non-indigenous grasses have been found to alter ecosystem properties (Christian and Wilson 1999). Since non-indigenous C 3 and native C 4 grasses differ in their photosynthetic pathways and wateruse efficiency, we hypothesized that the nonindigenous grasses may be depleting soil water levels resulting in reduced oak seedling growth and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Although this conversion is often attributed to grazing, exotic annuals have maintained their dominance in many areas that have now been excluded from livestock grazing for decades (30). Along with the displacement of the native perennial flora, this invasion has potentially increased nitrate leaching, altered fire regimes, and decreased carbon storage (29,(31)(32)(33).…”
mentioning
confidence: 99%